Associação entre coinfecção viral e o tempo de internação em lactentes com crise de sibilância - Coutinho, Sandra Eugenia (2013)
Introduction: the main causes of hospitalization in infants are wheezing episodes caused by seasonal viruses. The impact of infection by two or more viruses is not well established in the literature, especially the relationship between coinfection and clinical severity of the disease. Methods: In the present study, we evaluated the occurrence of infections and coinfections by respiratory viruses in infants with wheezing, as well as the association between coinfection and outcomes related to disease severity. This was a cross-sectional study with infants up to 12 months of age with acute wheezing, who were admitted to a pediatric unit. The study was conducted between September 2009 and September 2011. For identification of respiratory viruses, nasopharyngeal secretions were collected and, the samples were analyzed using the immunofluorescence and PCR for respiratory viruses. Results: 35.3% (42/119) of patients were negative for virus; 48.7% (58/119) were positive for one virus and 11.8% (14/119) for two viruses. The association of coinfection and severity measured by different periods of hospitalization, use of oxygen therapy and wheezing showed significant results. The higher were the number of virus identified; the higher the markers of severity. Conclusion: In this study, the coinfection with respiratory viruses in infants with wheezing influenced the severity of the clinical condition. In addition, rates of coinfection in infants admitted to the emergency hospital suggests that crowding of people in the same environment as well as the short distance between beds in emergency can be factors contributing to coinfection with respiratory viruses.